Education and social mobility at SMK Negeri 1 Sangatta Utara - Fitriani, Nurjannah Eka; Wardana, Haeril Kurniawan; Hidayat, M.Rozak; Yasin, Muhammad (Institute of Computer Science (IOCS), 2024)
Education in a broad sense develops the ability to recognize and understand emotional and intellectual weaknesses that are not divided by the dimensions of time and space. Similarly, education in the broadest sense encompasses the whole of life. One of the main factors that can affect social mobility is education. A good education can provide motivation to improve one's social and economic position. This article discusses the role of education on social mobility as well as the factors that influence social mobility through education, which is implemented by Sekolah Menengah Kejuruan Negeri 1 Sangatta Utara (SMK N 1). This article aims to understand the role of education on social mobility which aims to provide practical skills and knowledge that can be directly applied in the world of work as well as factors that affect social mobility through education such as the quality of education, availability of facilities, teacher support, and socio-economic background. This article was compiled using qualitative research methods by collecting data through interviews with teachers, students and parents, observations at school and literature review. The results show that the role of education in mobility, through internships and practical training in the world of work, which significantly increases their chances of getting a permanent job and improving their social status in the workplace, as well as in the factors that influence social mobility in education show that high-quality education in vocational schools provides a solid foundation for students to improve their social status through the development of skills and knowledge relevant to the labor market.